2015
DOI: 10.1097/ccm.0000000000000709
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pro-Adrenomedullin Levels Predict Mortality in Thoracic Surgery Patients

Abstract: In elective cardiac surgery, MR-pro-adrenomedullin measured between 6 and 18 hours after admission to the ICU is a better predictor of hospital mortality in comparison with the Acute Physiology and Chronic Health Evaluation IV score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Mid-regional proadrenomedullin (MR-proADM) is a peptide generated by multiple tissues in order to stabilise the microcirculation and protect against endothelial permeability [ 6 11 ], both of which are widely acknowledged to play a significant role in the pathophysiological host response to sepsis [ 12 , 13 ]. Indeed, MR-proADM levels are rapidly induced during the initial stages of sepsis development following burns [ 14 ] and neurological disorders [ 15 ], in response to invasive fungal infections in patients with septic shock [ 16 ], and in other conditions such as lower respiratory tract infections [ 17 19 ], lung transplantation [ 20 ] and thoracic surgery [ 21 ]. Thus, MR-proADM may be of significant clinical utility in the early risk stratification of patients with sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Mid-regional proadrenomedullin (MR-proADM) is a peptide generated by multiple tissues in order to stabilise the microcirculation and protect against endothelial permeability [ 6 11 ], both of which are widely acknowledged to play a significant role in the pathophysiological host response to sepsis [ 12 , 13 ]. Indeed, MR-proADM levels are rapidly induced during the initial stages of sepsis development following burns [ 14 ] and neurological disorders [ 15 ], in response to invasive fungal infections in patients with septic shock [ 16 ], and in other conditions such as lower respiratory tract infections [ 17 19 ], lung transplantation [ 20 ] and thoracic surgery [ 21 ]. Thus, MR-proADM may be of significant clinical utility in the early risk stratification of patients with sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…A preoperative value of 0.87 nmol/L in the pilot study of our group to predict the need for POS [35]; A preoperative value of 0.85 nmol/L in the study by Golubović et al to predict postoperative mortality in abdominal surgery [36]; A preoperative value of 0.77 ± 0.37 nmol/L in the study of Egyed et al [37]; A preoperative value of 1.3 nmol/L in the study referring to the prognostic capacity of mortality after TAVI [38]; A postoperative value of 3.2 nmol/L in the study for the prediction of mortality in the postoperative period of cardiac surgery [39].…”
Section: Discussionmentioning
confidence: 99%
“…It has been examined whether a panel of biomarkers (PCT, MR-proADM, CT-pro-endothelin-1, CT-pro-arginine vasopressin, and MR-pro-ANP), each of them separately or using the Acute Physiology and Chronic Health Evaluation IV score, has a greater significance in the prediction of intrahospital mortality. It has been shown that MR-proADM has the greatest significance in the first 6 to 18 hours after entering the ICU, even when its significance has been compared to the Acute Physiology and Chronic Health Evaluation IV score in elective cardiosurgery (17).…”
Section: Discussionmentioning
confidence: 99%